Avaliação do curso de ciências farmacêuticas da unidade acadêmica da UFAM em Itacoatiara: qualidade e efetividade a partir de uma perspectiva qualitativa de pesquisa. - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
In recent years, the Federal Institutions of Higher Education (IFES) created several undergraduate courses through the university expansion programs, aiming to double the number of vacancies and ensure the permanence of students in higher education in Brazil. These courses can be viewed as a production system. By enrolling in the university, its students integrate the system and go through an entire training process towards the completion of the course, graduates when they come out properly. This makes it possible to design new undergraduate courses as a vast field of research to production engineering. In this context, this research aimed to evaluate the quality and effectiveness of a course in Bachelor of Pharmaceutical Sciences in one of the campuses of the Federal University of Amazonas, based on the assessment tool of the INEP / MEC and allusions to productivity. For this, we conducted this research from the perspective of qualitative ethnographic case study type, and participant observation, document analysis, structured interviews and research strategies and also the participation of leaders, teachers, administrative staff and students of the institution. Data collection was done in three stages: first, we proceeded with observations in the physical structure and notes in the notebook field, making up some pictures, on Monday became the analysis and selection of institutional documents, and third, the participants were interviewed, with interviews recorded and transcribed verbatim. Data were analyzed using content analysis, generating themes, categories and subcategories of analysis. The results revealed that this production system began to operate during the deployment of an academic unit's permanent UFAM this campus, which required much effort to ensure an adequate human and physical infrastructure to meet the needs of users. It was found that the teaching staff of pharmacists reduced at the beginning made it difficult to plan the structure of the laboratory course; the materials management was identified as one of the weaknesses of the system; the mechanism of self-assessment of UFAM offers no support to the unit managers in making decision. The relevance of social and motivational aspects were adopted to study the effectiveness of the course, considering the contributions that can be given to health from a human framework willing to collaborate with internal processes.
Keywords: Avaliação de curso; Formação acadêmica; Enfermagem - estudo e ensino; Produtividade; Course evaluation; Academic education; Nursing - Study and teaching; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO